(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Perforation of the tympanic membrane may occur from various reasons. Most of these perforations heal spontaneously, whereas the remaining long-standing perforations that lead to recurrent ear discharge need tympanoplasty. Interlay Type 1 Tympanoplasty,a newer technique has shown promising results with higher success ratein terms of hearing gain and graft uptake. Objective: To analyze the results of interlay Type 1 Tympanoplasty in terms of graft uptake and hearing improvement in cases of inactive mucosal chronic otitis media (COM) with large central perforation. Methods: This is a prospective study of 24 months (January 2018 to December 2019) duration conducted in department of E.N.T, Khulna medical college, Khulna and data was collected from the 60 patients admitted for tympanoplasty. Results were calculated in terms of graft accepted or rejected and decrease in air bone gap. Result: The graft uptake rate in the present study was found to be 91.67% and the patients reported an improvement in terms of hearing. Pre operatively mean air bone gap was 26.5dBand post operatively after 12 weeks mean air bone gap improved to 17.58dB. Conclusion: Interlay Type 1 Tympanoplasty is an effective technique over conventional methods in terms of both graft uptake as well as hearing improvement in large central perforation. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 86-91